Effectiveness of peer pressure on computed tomography use for dizziness/vertigo patients. Issue 11 (March 2019) - Chuang, Po-Chun; Huang, Yi-Syun; Chiang, Charng-Yen; Zhang, E-Wai; Cheng, Fu-Jen
Abstract : Abstract: Dizziness/vertigo is a common complaint in the emergency department (ED). We aimed to evaluate the effect of peer pressure on decision making in emergency physicians (EPs) to use computed tomography (CT) for patients with dizziness/vertigo. We conducted a before-and-after retrospective case review of patients who visited the ED with dizziness/vertigo. EPs were categorized into 3 groups according to seniority (in years of experience: >12, 7–12, and <7). The rate of CT use for EPs, patient number, and CT use were e-mailed monthly to update the EP team on the benchmark rate and shape of the behavior. Among the 1657 (preintervention) and 1508 (postintervention) patients with dizziness/vertigo, 320 (19.3%) and 230 (15.3%), respectively, underwent brain CT. A decrease in the rate of CT use was observed in the postintervention group (odds ratio [OR] = 0.743, 95% confidence interval [CI] = 0.615–0.897), especially in junior EPs (years of experience, <7; OR = 0.667, 95% CI: 0.474–0.933) and younger patients (age, <60) (OR = 0.625, 95% CI: 0.453–0.857). The intervention strategy created peer pressure through e-mail reminders and decreased the rate of CT use for patients with isolated dizziness/vertigo, especially in junior EPs and younger patients.